Prinsip Kemanfaatan Ujrah pada Take Over Kredit Kepemilikan Rumah (KPR) di Bank Syariah melalui Pendekatan Maqāshīd Syarīah - Maudyna Fitria; Rahmadi Indra Tektona; Dyah Ochtorina Susanti (Prodi Hukum Ekonomi Syariah (Muamalah), 2022)
The ujrah system in the take over of home ownership loans in Islamic banks on the use of hawalah and qardh contracts, which are basically hawalah and qardh contracts, is a type of tabarru' contract which is helpful or voluntary and may not take profit. The existence of taking Ujrah or fees in take over KPR transactions by Islamic banks, of course, is a deviation with the meaning of tabarru', namely helping, but taking Ujrah in the hawalah contract is allowed based on the DSN fatwa Number 58/DSN-MUI/V/2007 concerning Hawalah bil Ujrah must based voluntarily and by agreement, although hawalah itself in the theory of Islamic law contracts is a tabarru or non-profit contract. The research method is a normative (doctrinal) research method, which examines or analyzes legal rules related to the object of this research, namely the ujrah system in take over in Islamic banks. So it can be concluded that the use of the ujrah system in the practice of taking over home ownership loans at Islamic banks has the characteristics of a fee-taking system for the benefit of goods or services, not to get excessive profits because it is helping.